PENGARUH ADIKSI GAME ONLINE TERHADAP PRESTASI AKADEMIK DAN INTERAKSI SOSIAL SISWA SEKOLAH DASAR - Ari Nur Kristanti; Yayan Ristiana; Daroe Iswatiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Online games are a highly concerning phenomenon in today's digital era. Online game addiction can cause problems in daily life. The prevalence of online game addiction has been increasing due to the ease of access to technology among children. This study aims to examine the influence of online game addiction on academic achievement and social interaction among elementary school-aged children.The study employed a quantitative approach with a survey method, involving 24 students from SD Muhammadiyah 1 Kota Malang and 28 students from MI Muhammadiyah 03. The results indicated a significant negative impact of online game addiction on students' academic performance. Additionally, online game addiction also affected the quality of social interactions, such as reduced communication with peers and family.These findings highlight the critical role of parents and teachers in monitoring children's online gaming time and supporting the development of their social and academic skills. Interventions, such as technology education and time management, can serve as preventive measures to mitigate the negative effects of online game addiction on children.